Dimension‐Based Design of Melt Electrowritten Scaffolds. Issue 22 (30th April 2018) - Hrynevich, Andrei; Elçi, Bilge Ş.; Haigh, Jodie N.; McMaster, Rebecca; Youssef, Almoatazbellah; Blum, Carina; Blunk, Torsten; Hochleitner, Gernot; Groll, Jürgen; Dalton, Paul D.
Abstract: The electrohydrodynamic stabilization of direct‐written fluid jets is explored to design and manufacture tissue engineering scaffolds based on their desired fiber dimensions. It is demonstrated that melt electrowriting can fabricate a full spectrum of various fibers with discrete diameters (2–50 µm) using a single nozzle. This change in fiber diameter is digitally controlled by combining the mass flow rate to the nozzle with collector speed variations without changing the applied voltage. The greatest spectrum of fiber diameters was achieved by the simultaneous alteration of those parameters during printing. The highest placement accuracy could be achieved when maintaining the collector speed slightly above the critical translation speed. This permits the fabrication of medical‐grade poly(ε‐caprolactone) into complex multimodal and multiphasic scaffolds, using a single nozzle in a single print. This ability to control fiber diameter during printing opens new design opportunities for accurate scaffold fabrication for biomedical applications. Abstract : The continuous direct writing of an electrically stabilized polymer jet is remarkably stable, with speed‐ and pneumatically driven diameter changes not requiring any applied voltage change. Using two poly(ε‐caprolactone) scaffolds as examples, the design with a spectrum of different fiber diameters allows for further variations of melt electrowritten products.